New evidence for flux cutting in type II superconductors. - LeBlanc, David. (University of Ottawa (Canada), 1992)
We present new evidence for cross flow and cutting of nonparallel flux lines in type II superconductors. A dramatic reversal is observed in the evolution of $B\sb{z}\sb{hole}$, the axial flux density in the cavity of a hollow cylinder when the magnitude of a helical magnetic field, $\vec H\sb{ext} = \\phi H\sb\phi + \ z H\sb{\rm II}$ is increased or decreased along the surfaces of the specimen. This turn around constitutes a 180$\sp\circ$ degree deviation from the predictions of the "classical" critical state framework (no flux line cutting). Measurements of the concurrent evolution of $\langle B\sb{z}\rangle \sb{wall}$, the axial flux density threading the wall of the hollow cylinder, complement the above data. The behaviour of $\langle B\sb{z}\rangle\sb{wall}$ is also in drastic disagreement with the "classical" picture of "one way" traffic of flux lines dictated solely by the change in magnitude of $\vec H\sb{ext}.$ These observations also provide strong support for our interpretation. Our account of these unexpected phenomena is based on the ideas of two way traffic of sublattices of nonparallel flux lines traversing each other via flux line cutting processes. We briefly review the classical critical state concept. The essential features of the flux cutting process, cross traversal of flux line sheets and attendant "breathing" modes are also outlined. Then the Generalized Critical State Model incorporating a phenomenological framework based on Maxwell's equations, standard physical constraints and two separate energy dissipation mechanisms is summarized. Finally we present our data curves and show in qualitative detail that the observed behaviour demonstrates that flux line cutting occurs and associated breathing in and out of non-parallel flux lines takes place across the surface of type II superconductors subjected to a varying $\vec H\sb{ext}.$
Keywords: Physics, Condensed Matter.